2021
DOI: 10.1021/acs.iecr.1c03517
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic Coupling of SnS2 Nanosheet Arrays with Ni/Fe Dual Metal and Ru Nanodots via a Cation Exchange Strategy for Overall Water Splitting

Abstract: The application of tin disulfide (SnS2) in electrochemical water splitting remains a challenging issue on account of its unsatisfactory intrinsic electron conductivity and electrocatalytic activity. In this work, the vertically aligned SnS2 nanosheet arrays with open porous mass transfer pathways are synthesized, while the rational surface modification of highly electrocatalytic active heteroatoms (Ni/Fe or Ru) onto the SnS2 surface is achieved by a cation exchange strategy. The as-prepared Ni/Fe dual-metal-do… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 58 publications
1
6
0
Order By: Relevance
“…The overpotentials of the pristine SnS 2 monolayer for OER and ORR are higher (1.72 and 1.39 V) than those of TM/SnS 2 except Fe/SnS 2 for ORR, suggesting that the pristine SnS 2 monolayer is not an efficient electrocatalyst for OER and ORR and the TM single atom anchored on the surface of SnS 2 can improve its catalytic performance. These results agree well with the reported studies ,, that TM doping can effectively improve the catalytic performance of catalysts for OER and ORR. To better understand the OER/ORR catalytic mechanism of SnS 2 monolayer-supported TM atoms, we first investigate the catalytic performance of the pristine SnS 2 monolayer, and the corresponding free energy diagrams at U = 0 V and 1.23 V are shown in Figure S1.…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…The overpotentials of the pristine SnS 2 monolayer for OER and ORR are higher (1.72 and 1.39 V) than those of TM/SnS 2 except Fe/SnS 2 for ORR, suggesting that the pristine SnS 2 monolayer is not an efficient electrocatalyst for OER and ORR and the TM single atom anchored on the surface of SnS 2 can improve its catalytic performance. These results agree well with the reported studies ,, that TM doping can effectively improve the catalytic performance of catalysts for OER and ORR. To better understand the OER/ORR catalytic mechanism of SnS 2 monolayer-supported TM atoms, we first investigate the catalytic performance of the pristine SnS 2 monolayer, and the corresponding free energy diagrams at U = 0 V and 1.23 V are shown in Figure S1.…”
Section: Resultssupporting
confidence: 93%
“…As one member of the LMD family, pristine SnS 2 is scarcely employed as a hydrogen evolution reaction (HER), OER, and ORR catalyst compared with MoS 2 because there are poor active sites in pristine SnS 2 . However, there are extensive investigations on SnS 2 nanostructures in energy storage and conversion fields because they are sustainable and abundant in nature. Therefore, scientists have been making an effort to improve the poor active sites of SnS 2 for electrocatalytic reactions. For example, Liu et al reported that the introduction of Pt in SnS 2 can enhance the active site of HER due to the reduction of the reaction barrier. Moreover, Jiang et al reduced the OER overpotential of the SnS 2 nanosheet array by Co doping and demonstrated that the Co-doped SnS 2 exhibited efficient catalytic activity in 1M KOH solution for OER.…”
Section: Introductionmentioning
confidence: 99%
“…38 Pristine SnS 2 shows hexagonal lattice with (Figure 1a) broad diffraction peaks at 15.56, 28.52, 50.28°that can be indexed to the (001), (100), and ( 110) planes (JCPDS # 23-0677). 39 The broad peaks together with the low intensity of the (001) peak suggested the growth of SnS 2 layers in the (100) direction and the thin-layer nature of the as-synthesized pristine SnS 1a), implying that the photodeposition of the CoPi cocatalyst did not alter the crystalline structure of the CdS nanorods. In addition, the small peak observed at 13.24°( marked with #) can be attributed to diffraction from the (020) plane of Co 3 (PO 4 ) 2 •8H 2 O, confirming the effective growth of CoPi nanoclusters on CdS surface by the photodeposition method.…”
Section: Structure and Morphologymentioning
confidence: 97%
“…Therefore, the extension of MACs to a broad spectrum of catalytic active materials (e.g., metal sulfides and phosphides) shows great potential. [50][51][52] More importantly, cation exchange is a rapid low-temperature process that can be used to kinetically (rather than thermodynamically) generate new compositions and phases. [40] Thus, cation exchange on a parent support can be shape-conserving and can be used to preserve the metastable or non-equilibrium states of the support, thereby enabling the generation of complexity in MACs.…”
Section: Structure and Composition Versatility Of Macsmentioning
confidence: 99%